(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2026)
This article examines the improvement of the methodology for forming students’ independent reading and text working skills in home education. The study emphasizes that home-based learning requires a flexible, individualized, and pedagogically coordinated approach, because students who study at home often have fewer opportunities for regular classroom interaction, collective discussion, and continuous teacher supervision. In this context, independent reading is considered not only as the ability to read texts outside the classroom, but also as a complex competence that includes understanding, selecting information, identifying the main idea, analyzing textual structure, interpreting meaning, expressing personal opinions, and applying acquired knowledge in practical situations. The article substantiates the importance of adapted texts, differentiated tasks, parental support, digital learning resources, and systematic monitoring in developing students’ reading independence. Particular attention is given to the cooperation between teacher, student, and family as a key condition for organizing effective text-based learning activities at home. The proposed methodological approach may be useful for future teachers, primary and secondary school educators, and specialists involved in inclusive and individualized education.